2019
DOI: 10.3389/fmicb.2019.01940
|View full text |Cite
|
Sign up to set email alerts
|

A Mathematical Model of Campylobacter Dynamics Within a Broiler Flock

Abstract: Globally, the bacterial genus Campylobacter is one of the leading causes of human gastroenteritis, with its primary route of infection being through poultry meat. The application of biosecurity measures is currently limited by a lack of understanding of the transmission dynamics within a flock. Our work is the first to undertake a mathematical modeling approach to Campylobacter population dynamics within a flock of broilers (chickens bred specifically for meat). A … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 48 publications
0
25
0
Order By: Relevance
“…One can also observe slight oscillating behaviour in the total number of infections across a few weeks, most notably in the May to September period. Experimental and theoretical studies have both confirmed the presence of these oscillations 2117 , caused by the immune response within each chicken creating predator-prey style oscillations between the immune system and invading bacteria. One can also note from figures 1 to 3 that C. jejuni appears to be the most frequently appearing species of Campylobacter in the summer months, before C. coli takes over as the most frequently appearing species in the winter.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…One can also observe slight oscillating behaviour in the total number of infections across a few weeks, most notably in the May to September period. Experimental and theoretical studies have both confirmed the presence of these oscillations 2117 , caused by the immune response within each chicken creating predator-prey style oscillations between the immune system and invading bacteria. One can also note from figures 1 to 3 that C. jejuni appears to be the most frequently appearing species of Campylobacter in the summer months, before C. coli takes over as the most frequently appearing species in the winter.…”
Section: Discussionmentioning
confidence: 92%
“…Note however from figure 2 that, despite the higher number of C. jejuni STs, each week is primarily dominated by only two or three STs. This phenomena was found through theoretical study to be a result of stochastic drivers within the system, as opposed to any demographic advantages unique to certain STs 17 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations